Case Report: Selexipag in pediatric pulmonary hypertension: Initiation, transition, and titration - Jenna M. Faircloth; Neelam D. Bhatt; Corey A. Chartan; Ryan D. Coleman; Natalie Villafranco; Fadel E. Ruiz; Raysa Morales-Demori; Elise Whalen; Erin Ely; Rozmeen Fombin; Nidhy P. Varghese (Frontiers Media S.A., 2023)
Selexipag, a selective prostacyclin receptor agonist, is approved for treating pulmonary arterial hypertension in WHO Group 1 adult patients. Compared to parenteral prostacyclin formulations, selexipag offers a significant improvement in patient's and caregiver's quality of life because of its oral formulation, frequency of administration, and mechanism of action. Although experience in the pediatric population is limited and selexipag is not FDA-approved for use in the pediatric pulmonary hypertension population, many US pediatric centers are expanding the use of this therapy to this younger population. We report our institution's experience in the use of selexipag to treat pulmonary hypertension in children under 10 years of age, between 10 and 30 kg. Seven patients were initiated on selexipag therapy including de novo initiation and transition from intravenous treprostinil to oral selexipag. All patients were on stable background therapy with phosphodiesterase-5 inhibitor and endothelin receptor antagonist therapies at baseline. All patients reached their planned goal selexipag dose during admission without the need for changes to the titration schedule and without hemodynamic deterioration. In our experience, oral selexipag is safe and well-tolerated in young pediatric patients with pulmonary hypertension. Based on our favorable experience, we developed an institution-specific selexipag process algorithm for continued successful use in the pediatric population.